In-silico Design and Testing of Tetra-Primer Arms-PCR for SNPs-Based Identification of Sumatran Tiger (Panthera tigris sumatrae): ARMS-PCR SNP Identification of Sumatran Tiger - Asrori, Ikrima; Novarino, Wilson; Tjong, Djong Hon; Roesma, Dewi Imelda (Journal of Tropical Life Science, 2026)
The Sumatran tiger (Panthera tigris sumatrae) is a subspecies of tiger classified as critically endangered by the International Union for Conservation of Nature (IUCN) due to poaching and illegal trade. In the law enforcement process, it is very important to ensure that the sample is indeed from a Sumatran tiger. Seized samples from illegal trade cannot be identified based on their morphology because they have been degraded and processed into other forms. Previous studies have reported the use of molecular markers for Sumatran tiger identification, which involve lengthy procedures and analyses. Therefore, for a more effective identification process, faster and more accurate techniques are needed. This study aims to design tetra primers for the identification of Sumatran tiger subspecies, particularly from incomplete confiscated samples, using the Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR) technique based on Single Nucleotide Polymorphism (SNP) markers. The primers were designed using the Primer1 application and validated in silico with CloneManager and NCBI BLAST, as well as through direct testing on Sumatran tiger blood samples. The design results showed one pair of primers with optimal specifications, producing G allele fragments (452 bp), A allele fragments (408 bp), and internal control fragments (819 bp). Specificity testing results indicated that all samples were Sumatran tigers, with amplification bands at 452 bp and 819 bp. These results demonstrate that the developed tetra-primer ARMS-PCR assay provides a rapid and practical molecular approach for identifying Sumatran tiger samples, particularly for forensic verification of confiscated wildlife materials.